The Relationship Between Coping Strategies, Quality of Life, and Mood in Patients with Incurable Cancer - Nipp, Ryan D. (Cancer, 2016)
BACKGROUND: Patients with incurable cancer face many physical and emotional stressors, yet little is known about their coping strategies or the relationship between their coping strategies, quality of life (QOL) and mood. METHODS: As part of a randomized trial of palliative care, this study assessed baseline QOL (Functional Assessment of Cancer Therapy–General), mood (Hospital Anxiety and Depression Scale), and coping (Brief COPE) in patients within 8 weeks of a diagnosis of incurable lung or gastrointestinal cancer and before randomization. To examine associations between coping strategies, QOL, and mood, we used linear regression, adjusting for patients’ age, sex, marital status, and cancer type. RESULTS: PARTICIPANT SAMPLE: There were 350 participants (mean age, 64.9 years), and the majority were male (54.0%), were married (70.0%), and had lung cancer (54.6%). Most reported high utilization of emotional support coping (77.0%), whereas fewer reported high utilization of acceptance (44.8%), self-blame (37.9%), and denial (28.2%). Emotional support (QOL: β = 2.65, P < .01; depression: β = −0.56, P = .02) and acceptance (QOL: β = 1.55, P < .01; depression: β = −0.37, P = .01; anxiety: β = −0.34, P = .02) correlated with better QOL and mood. Denial (QOL: β = −1.97, P < .01; depression: β = 0.36, P = .01; anxiety: β = 0.61, P < .01) and self-blame (QOL: β = −2.31, P < .01; depression: β = 0.58, P < .01; anxiety: β = 0.66, P < .01) correlated with worse QOL and mood. CONCLUSION: Patients with newly diagnosed, incurable cancer use a variety of coping strategies. The use of emotional support and acceptance coping strategies correlated with better QOL and mood, whereas the use of denial and self-blame negatively correlated with these outcomes. Interventions to improve patients’ QOL and mood should seek to cultivate the use of adaptive coping strategies.